A relação do Serviço Social com as lutas sociais no Brasil nas décadas de 1970-1990: um esforço coletivo de investigação sobre a questão da natureza da dimensão ético-política profissional (2024)
The article presents the historical and theoretical-methodological assumptions of an ongoing research proposal on the nature of the ideopolitical dimension and the particularity of the praxis philosophy in the process of development and consolidation of the ethical-political project of Brazilian Social Service. In this sense, elements that shaped the nature of the ideological-political dimension in the Reconceptualization Movement and the particularity of its characterization in the Brazilian reality during the 1970s and 1980s are explained. We explain, here, the processes that constituted the sociopolitical bases that made it possible to challenge conservatism and build the ethical-political project of Brazilian Social Service - processes that express the development of bibliographic and documentary studies undertaken so far by the authors, therefore dealing with a partial presentation of the results of the investigation . In this context, the analytical axes of the research proposal on screen are demarcated, namely: 1. the nature of the ideo-political dimension of the profession addressed in the relationship between class struggle/societal projects of the subordinate classes and professional projects and 2. the bases sociopolitical aspects that permeate the aforementioned relationship, demarcating with special attention the theoretical and ideopolitical accumulations that underlie them.